Online learning for individuals with dyslexia: A literature review - Pang, L.; Chen, Chwen Jen; Anding, P.N.; Teh, Chee Siong (International Journal of Learning and Teaching, 2015)
Although there are relative researches on dyslex-ia, little is known about the difficulties of those with dyslexia faced when exploring internet for learning. This paper con-ducted a review of papers to investigate the existing re-searches and work done related to online learning for indi-viduals with dyslexia. It is aimed to identify the currently available knowledge about dyslexia and online learning. The results of the searches clearly show that there are limited researches on the needs of people with dyslexia and prob-lems encountered in online learning. Most of researches context revolved in higher education where the samples are adolescent and adults. From the aspect of the media used in online learning, synchronous and asynchronous text based chatting were more focused in research. Based on the re-view of the nine articles, three main research themes includ-ing design guidelines, engagement with different media types and online learning systems for individual with dys-lexia were identified. It is reviewed that although online learning has a large acknowledgement for its benefits in distance learning or personalized learning, the guidelines for current online learning design may not beneficial all the users such as people with dyslexia. Based on the review, the authors of this paper have identified a need for the applica-tion of specific design principles in the development of online learning accessibility to provide equal accessibility and inclusive education for all levels.